Characteristics of U.S. Nursing Homes with COVID‐19 Cases - Abrams, Hannah R. (J Am Geriatr Soc, 2020)
BACKGROUND/OBJECTIVES: The 2019 coronavirus disease (COVID‐19) has been documented in a large share of nursing homes throughout the United States, leading to high rates of mortality for residents. To understand how to prevent and mitigate future outbreaks, it is imperative that we understand which nursing homes are more likely to experience COVID‐19 cases. Our aim was to examine the characteristics of nursing homes with documented COVID‐19 cases in the 30 states reporting the individual facilities affected. DESIGN: We constructed a database of nursing homes with verified COVID‐19 cases as of May 11, 2020, via correspondence with and publicly available reports from state departments of health. We linked this information to nursing home characteristics and used regression analysis to examine the association between these characteristics and the likelihood of having a documented COVID‐19 case. SETTING: All nursing homes from 30 states that reported COVID‐19 cases at the facility‐level. PARTICIPANTS: Nursing home residents in states reporting data. MEASUREMENTS: Whether a nursing home had a reported COVID‐19 case (yes/no), and conditional on having a case, the number of cases at a nursing home. RESULTS: Of 9,395 nursing homes in our sample, 2,949 (31.4%) had a documented COVID‐19 case. Larger facility size, urban location, greater percentage of African American residents, non‐chain status, and state were significantly (P < .05) related to the increased probability of having a COVID‐19 case. Five‐star rating, prior infection violation, Medicaid dependency, and ownership were not significantly related. CONCLUSION: COVID‐19 cases in nursing homes are related to facility location and size and not traditional quality metrics such as star rating and prior infection control citations. J Am Geriatr Soc 68:1653‐1656, 2020.